Evaluation of Flood Handling at Seminyak Way II, in The Tukad Mati Drainage Sub System - I Gusti Ngurah Kerta Arsana; Mawiti Infantri Yekti; Dewa Ayu Utari Winandari (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
Flood is a natural phenomenon that often occurs in several areas of Badung Regency. Losses result in damage to buildings, roads, and other public facilities. Floods are caused by a more sloping land topography, changes in land use to dense settlements, and soil conditions. This study aims to deal with flooding by evaluating the existing canal on Jalan Kunti II Seminyak. The method used for testing data consistency is the RAPS (Rescaled Adjusted Partial Sums) method. The distribution used is Log Person Type III. Testing of frequency distribution used the Smirnov – Kolmogorov Test and the Chi-Square Test. Analysis of rainfall intensity using the Mononobe formula. Calculation of planned flood discharge (Q) uses the Rational method, Nakayasu method, and theoretical discharge control for 2, 5, 10, and 25-year return periods with the existing channel capacity. The result of the analysis shows that the theoretical discharge with a return period has met of planned flood discharge so that the drainage on Jalan Kunti can accommodate the planned flood with a return period of 10 years. Where the drainage capacity of Jalan Kunti is 0,412 m3/second & 0,461 m3/second. The drainage ditch with a capacity of 200 m3/second to Tukad Mati has not been able to accommodate the planned flood discharge for the 25-year return period of 242.33 m3/second. The Tukad Mati channel for the existing Q 675,825 m3/second has been able to accommodate the flood discharge Q at the 25-year return period of 314.49 m3/second.